Analisis Makna Komunikasi Noverbal pada Prosesi Pernikahan Adat Jawa Pakem Surakarta - M. Syamsul Ma’arif; Siti Mayasaroh (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This article explores the symbolic meanings embedded in nonverbal communication present during the series of traditional Javanese wedding ceremonies from the Pakem Surakarta tradition. The purpose of this study is to identify and interpret the cultural symbols hidden in each phase of the ritual, such as the exchange of kembar mayang, stepping on eggs, sindur binayang, kacar-kucur, dhahar klimah, and sungkeman. The approach used in this study is a descriptive qualitative method with an ethnographic communication framework. Data was collected through direct observation and in-depth interviews with community leaders or wedding officiants, as well as cultural figures from the villages of Cendono and Bakalan in Pasuruan Regency. The findings of the study emphasize that the nonverbal symbols present in the ceremony carry meanings related to values of responsibility, role equality, purity, blessings, and affection, which are directed not only toward the bride and groom but also to the extended families and the surrounding community. Therefore, Javanese traditional marriage is not merely a ritual event, but also a means of preserving cultural teachings and spiritual values across generations. The ceremony reflects a strong bond between individuals, families, and the community, fostering social and spiritual harmony. Furthermore, this ceremony serves as a medium for strengthening intergenerational relationships within society, with the aim of preserving traditions and moral values in social life. Thus, a traditional Javanese wedding not only symbolizes the union of two individuals but also acts as a medium for maintaining and spreading cultural and spiritual values within the community.